275 Feeding a whole-cell inactivated Pichia guilliermondi yeast to gestating and lactating sows in a commercial production system. (30th November 2020) - Thayer, Morgan T; Garcia, Ricardo M; Duttlinger, Alan W; Mahoney, Julie F; Schinckel, Allan P; Asmus, Matthew D; Jones, Daniel B; Dunn, James L; Richert, Brian T
Abstract: A total of 606 sows (PIC 1050) and their progeny (PIC 1050×280) were used to determine if feeding gestating and lactating sows a proprietary strain of Pichia guilliermondi as a whole-cell inactivated yeast product (WCY; CitriStim, ADM Animal Nutrition, Quincy, IL) improves sow and litter performance in a commercial production system. Once confirmed pregnant at d 35 post-breeding pregnancy check, sows were fed either a basal gestation control (CON) diet (0.55% SID Lysine) or the control diet fortified with 0.15% (1.36 kg/ton) of the WCY replacing corn in the CON diet. Dietary treatments were also fed in lactation (1.05% SID Lysine) once sows were moved into farrowing crates on approximately d 112 of gestation until weaning. Sows supplemented with WCY in gestation and lactation had a greater number of total born piglets by 0.45 pigs (P=0.040), born alive (P< 0.04), heavier born alive litter weight (P< 0.001), and greater post cross-foster litter size (P< 0.001) compared to CON fed sows. Litter size at weaning was increased by 0.54 pigs when sows were fed WCY compared to CON (P< 0.001). However, the average piglet weaning weights from CON fed sows were heavier by 0.35 kg compared to WCY (P< 0.001). This increase in body weight of piglets from CON fed sows is partially explained by their 0.93 days longer lactation (P< 0.001), and may also be due to the smaller litter size nursed throughout lactation. The percent of litters treated for scours decreased from 38.3% to 14.2% when sows were fed WCY (P< 0.001). The distribution of birth weights by body weight range was not different (P=0.2461) between treatments. In conclusion, feeding gestating and lactating sows a proprietary strain of Pichia guilliermondi as a whole-cell inactivated yeast product increased the number of piglets born and number weaned as well as decreased the prevalence of scours during lactation.